Lung exposure to lipopolysaccharide causes atherosclerotic plaque destabilisation. Issue 1 (23rd March 2016) - Jaw, Jen Erh; Tsuruta, Masashi; Oh, Yeni; Schipilow, John; Hirano, Yuki; Ngan, David A.; Suda, Koichi; Li, Yuexin; Oh, Jin Young; Moritani, Konosuke; Tam, Sheena; Ford, Nancy; et al.
Epidemiological studies have implicated lung inflammation as a risk factor for acute cardiovascular events, but the underlying mechanisms linking lung injury with cardiovascular events are largely unknown. Our objective was to develop a novel murine model of acute atheromatous plaque rupture related to lung inflammation and to investigate the role of neutrophils in this process. Lipopolysaccharide (LPS; 3 mg·kg −1 ) or saline (control) was instilled directly into the lungs of male apolipoprotein E-null C57BL/6J mice following 8 weeks of a Western-type diet. 24 h later, atheromas in the right brachiocephalic trunk were assessed for stability ex vivo using high-resolution optical projection tomography and histology. 68% of LPS-exposed mice developed vulnerable plaques, characterised by intraplaque haemorrhage and thrombus, versus 12% of saline-exposed mice (p=0.0004). Plaque instability was detectable as early as 8 h post-intratracheal LPS instillation, but not with intraperitoneal instillation. Depletion of circulating neutrophils attenuated plaque rupture. We have established a novel plaque rupture model related to lung injury induced by intratracheal exposure to LPS. In this model, neutrophils play an important role in both lung inflammation and plaque rupture. This model could be useful for screening therapeutic targets to prevent acute vascular events related to lung inflammation. Neutrophils play an important role in atherosclerotic plaque vulnerability related to LPS-induced lung inflammation http://ow.ly/Y7dWW